Spectropolarimetric observations of the CIZA J2242.8+5301 northern radio relic: no evidence of high-frequency steepening. Issue 2 (7th August 2020) - Loi, F; Murgia, M; Vacca, V; Govoni, F; Melis, A; Wittor, D; Beck, R; Kierdorf, M; Bonafede, A; Boschin, W; Brienza, M; Carretti, E; et al.
ABSTRACT: Observations of radio relics at very high frequency (>10 GHz) can help to understand how particles age and are (re-)accelerated in galaxy cluster outskirts and how magnetic fields are amplified in these environments. In this work, we present new single-dish 18.6 GHz Sardinia Radio Telescope and 14.25 GHz Effelsberg observations of the well-known northern radio relic of CIZA J2242.8+5301. We detected the relic which shows a length of ∼1.8 Mpc and a flux density equal to S_14.25 GHz=(9.5± 3.9) mJy and S_18.6 GHz=(7.67± 0.90) mJy at 14.25 and 18.6 GHz, respectively. The resulting best-fitting model of the relic spectrum from 145 MHz to 18.6 GHz is a power-law spectrum with spectral index α = 1.12 ± 0.03: no evidence of steepening has been found in the new data presented in this work. For the first time, polarization properties have been derived at 18.6 GHz, revealing an averaged polarization fraction of \! 40 per cent and a magnetic field aligned with the 'filaments' or 'sheets' of the relic.